The influence of the ability to understand mathematics concepts based on van hiele's level of thinking on the learning outcomes of mathematics education students - Arlianti, Nofyta; Kamid, Kamid; Marzal, Jefri; Hasibuan, Muhammad Haris Effendi (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The aim of this research is to find out whether there is an influence on the ability to understand mathematical concepts based on Van Hiele theory on the learning outcomes of STKIP Muhammadiyah Sungai Penuh students. The research method that will be carried out is associative (correlational) research. Sample determination was carried out using random sampling technique or determining samples randomly after carrying out a normality test, test homogeneity and equality of means tests. The results of the calculations carried out obtained the calculated r value = 0.5 46 and r table = 0.444, apparently r count > r table , then it can be concluded that H 1 accepted , so it can be concluded that there is a significant relationship between learning interactions and results learn mathematics with interpretation Enough. Coefficient of determination (r)2 = 0.2981 . So the magnitude of the relationship between variable X and variable Y is 29.81 %. This means that the relationship between the ability to understand mathematical concepts and the learning outcomes of transformation geometry is 29.81 %.